Mobile Blood Donation Application - Hassan, Otman Mohamed M. (2010)
The importance of blood in human existence and wellbeing cannot be underrated. Blood has been regarded as the basis of human living, thus if it is not in short of, human health might be at risk. Thus blood banking and blood donation in any medical operation for saving human's life must be readily available. In this study, the researcher proposed the development of a WAP-based blood application system that enables voluntary blood donors to apply to donate blood anywhere and at anytime, with the aim of solving the problem experience in the traditional blood donation application.